The effects of healthy aging on the mnemonic benefit of survival processing. - Stillman, Chelsea; Coane, Jennifer; Profaci, Caterina; Howard, James; Howard, Darlene (Memory & Cognition, 2014)
A number of studies have shown that information is remembered better when it is processed for its survival relevance than when it is processed for relevance to other, non-survival-related contexts. Here we conducted three experiments to investigate whether the survival advantage also occurs for healthy older adults. In Experiment 1, older and younger adults rated words for their relevance to a grassland survival or moving scenario and then completed an unexpected free recall test on the words. We replicated the survival advantage in two separate groups of younger adults, one of which was placed under divided-attention conditions, but we did not find a survival advantage in the older adults. We then tested two additional samples of older adults using a between- (Exp. 2) or within- (Exp. 3) subjects design, but still found no evidence of the survival advantage in this age group. These results suggest that, although survival processing is an effective encoding strategy for younger adults, it does not provide the same mnemonic benefit to healthy elders.